Temporal lift with repositioning of the orbicular muscle and eyebrow tail - Ticiano Cesar Teixeira Cló; Walter Ferraz Flavio; Felipe Xavier Cló; Guilherme do Valle Castro Ribeiro (Revista Brasileira de Cirurgia Plástica, 2022)
Introduction: The superficial musculoaponeurotic system (SMAS) is the best structure we have at our disposal to elevate and reposition the face and neck in the facelift. However, in the temporoorbital region, this structure is often neglected. In the search for a simple, efficient and safe solution to treat temporoorbital droop, the author describes a temporal lift tactic with eyebrow tail repositioning to treat aging and sagging of the temporoorbital region.Methods: Treatment was performed in 358 patients between 2017 and 2020 in complete or temporary lifts. Only 30 were included in the article because they were exclusively submitted to temporal lifts, with or without blepharoplasty. Through a broken marginal intracapillary incision in the temporal region and with supraSMAS detachment, musculoaponeurotic treatment of the orbitotemporal region was performed, in addition to excess skin resection.Results: The tactic presented was efficient in lifting and opening the tail of the eyebrows in all treated cases, in addition to the effect of loss of contractile function of the lateral portion of the orbicularis muscle, with a significant improvement in periorbital wrinkles and orbitotemporal sagging.Conclusion: The effectiveness and excellent results achieved with the described operative tactic, associated with the scarcity of isolated or specific treatment options for the orbitotemporal region, make the proposed temporoorbital lift an excellent alternative for the rejuvenation of this region.